PENGARUH MEDIA PEMBELAJARAN PAPAN NUMERASI NILAI TEMPAT (PENAT) TERHADAP MINAT BELAJAR SISWA KELAS III PADA MATA PELAJARAN MATEMATIKA DI SDN WARUBERON - Frida Aristi Indriani; Muhammad Thamrin Hidayat; Nafiah; Sri Hartatik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted with the aim of examining the effect of the Place Value Numeracy Board learning media (PENAT) on the learning interest of 3rd-grade students, particularly in mathematics with the topic of place value. This study employed a quantitative research approach using a Pre-Experimental Design type: One Group Pretest-Posttest. The sample consisted of all 22 students in the 3rd grade, or in other words, a saturated sampling technique was used, as the entire population was included as the sample. Data collection in this study used a learning interest questionnaire. For data analysis, the Shapiro-Wilk normality test was used because the sample size was small (less than 30 students). Meanwhile, for hypothesis testing, the Paired Sample T-Test was used. Based on the results of data analysis, it was found that the average learning interest score of 3rd-grade students before the treatment (pretest) was 46.54, while the average score after the treatment (posttest) was 52.09. This means that the average learning interest in mathematics increased by 11.92%. Moreover, the result of the t-test using SPSS version 26 showed a significance value of 0.008, which means 0.008 < 0.05 (H₀ is rejected and H₁ is accepted). However, the correlation value between the pretest and posttest data was found to be -0.276, indicating a weak relationship between the two tested variables. Therefore, it can be concluded that the PENAT learning media has an effect on the mathematics learning interest of 3rd-grade students, but the effect is considered weak. This is due to the lack of a strong relationship between the two tested variables, indicating that PENAT media has only a weak influence on students’ interest in learning mathematics.